Analisis Media Pembelajaran Digital Berbasis Etnomatematika terhadap Kemampuan Pemecahan Masalah Siswa SD - Fahira Aurumida Rahmah; Ika Fitri Apriyani; Agnestasia Ramadhani (Kilau Publishing, 2025)
Problem-solving ability is a fundamental competency in mathematics that should be cultivated from the elementary school level. However, many students struggle to develop this skill due to the abstract nature of mathematics instruction and its limited contextual relevance. This study investigates the effect of ethnomathematics-based interactive learning media on the mathematical problem-solving ability of fifth-grade elementary school students in the topic of the perimeter of plane figures. A quasi-experimental method with a pretest–posttest control group design was employed. The participants were 38 fifth-grade students from SDN 1 Sukamanah, divided into an experimental group and a control group, each comprising 19 students. The experimental group was taught using ethnomathematics-based interactive media, while the control group received instruction through PowerPoint-based media. The research instrument consisted of a problem-solving test, and data were analyzed using the Wilcoxon Signed-Rank test and the independent t-test. The findings revealed a significant improvement in problem-solving ability in both groups, with p = 0.000 (r = 0.813) for the experimental group and p = 0.001 (r = 0.777) for the control group. However, the independent t-test on the posttest scores indicated p = 0.446 (d = 0.24), suggesting no statistically significant difference between the two groups. Nevertheless, the higher average score of the experimental group reflects a positive tendency toward the use of ethnomathematics-based interactive learning media.